SPECIFICS OF MOTIVATION IN COMBAT SPORTS - Jelena Ilić; Dragoljub Višnjić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Motivation can be defined as conscious or unconscious experience that serves as a factor that determines a person's behavior or her social action in a given situation. So far, various studies had identified over 100 different factors that explain why people engage in sports. However, the reasons for sports participation may differ depending on gender and sports' discipline. Therefore, in this paper were examinated whether there is a difference in the motives for sports participation among athletes engaged in different types of combat sports, and whether there is a difference in the motivation of male and female. The sample comprised 265 athletes (173 male and 92 female) who practiced karate, kick boxing, fencing, taekwondo, jiu jitsu, savate and kyokushin kaikan. Athletes were offered 10 reasons for sports participation that were to be ranked according to importance. The results showed that the love and health of the most important reasons for sports' participation and that is the least important reason was the wish of parents and good look. Also, it appears that health as a reason for playing sports was important to practice karate, savate, kick boxing, and success was the most important reason to deal with fencing. The desire of parents as the reason was the least important in kyokushin kaikan. The only statistically significant difference in gender appeared in ranking of money. Money was far less significant reason for the females. One can therefore conclude that there are certain peculiarities in motivation for sport among athletes of different combat sports and that kind of sport, more than gender differences contribute to these differencies.